Novel method to simulate large-scale thermal city models. (15th August 2018) - Nageler, P.; Schweiger, G.; Schranzhofer, H.; Mach, T.; Heimrath, R.; Hochenauer, C.
Abstract: This study presents a method used to simulate large-scale thermal models of cities that achieves two improvements compared to the state-of-the-art techniques: 1) Current state-of-the-art methods cannot simulate the dynamic interaction between subcomponents of a smart energy system at urban scale. This method proposes detailed dynamic simulation approaches for large-scale thermal models. 2) Currently applied co-simulation frameworks are not applicable to large-scale models. In the present study, the dynamic building simulation tool IDA Indoor Climate and Energy, which uses parallelization methods for large-scale models, is coupled with a co-simulation platform. The methods are applied to a semi-virtual case study, which consists of 1561 buildings and a new development area. The building stock is analyzed using an automated method based on publicly available data. In contrast, the virtual urban development area is investigated using a co-simulation framework with three dynamic simulation tools: IDA Indoor Climate and Energy for buildings (256 thermal zones and 29 heating systems), TRNSYS for the energy supply unit and Dymola/Modelica for the district heating network. The influence of co-simulation on the accuracy and on the computation time are investigated. The major finding of this study is that the computation time can be significantly reduced by decoupling methods. Highlights: Detailed dynamic simulation methods were developed for large-scale urban districts. A five-step workflow was introduced to model the dynamic interactions in districts. Buildings can be modeled within this framework at any degree of detail. A co-simulation framework was applied using variable timestep simulation. A co-simulation interface for IDA Indoor Climate and Energy was presented.